A systematic review on intervention programs to improve activity of daily living status and health related quality of life - Al Thomali, Majed Eida; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza; Kadir @ Shahar, Hayati; Mohammed Gabbad, Abdelsafi Abbas (Community Health Society Malaysia, 2017)
Background: Health related quality of life is gaining importance in examining people’s health outcomes. It is related to how good or bad people’s lives are, and to the degree of their overall wellbeing and life satisfaction level. Independency in self-care and basic activity of daily living is among the most crucial elements that could potentially affect people’s health related quality of life. The objectives of this review are to determine related studies that examined various interventions to improve the functional ability of patients with chronic diseases or injuries on health related quality of life and to identify the most common types of interventions, instruments, as well as studies designs. Materials and Methods: Literature review was performed through an electronic search of the related studies using the words “Activity of Daily Living”, and “Intervention”. Different electronic search engines were utilized, including PubMed, Science Direct, CINHAL and Medline. A specific search criterion were applied to include scientific journal articles with experimental design, written in English language and published from 2010 to 2016. Those articles that did not measure activity of daily living and health related quality of life together using standardized measures, pilot study or still in proposal stage, were excluded. Result: Thirty six experimental studies were eligible for inclusion. Twelve studies conducted on elderly, 7 for stroke, 6 for dementia whereas 9 studies for different kind of health conditions. Among those 36 studies, 26 studies were Randomized Control Trial design while 10 studies were quasi or other type of experimental design. Conclusion: Randomized Control Trials was used more frequently as an experimental design. Most of the interventions were rehabilitation and physiotherapy in nature. Barthel index was identified to be the most common instrument used to measure activity of daily living, whereas SF36 and EQ5D instruments were most commonly used for health related quality of life.